Improvement of operational management of hygiene and labor safety on the basis of assessment of occupational hazard - Kruzhilko, O. Ye.; Tkalych, I. M.; Polukarov, O. I.; Кружилко, О. Є.; Ткалич, І. М.; Полукаров, О. І. (КПІ ім. Ігоря Сікорського, 2019)
The purpose of the work is to provide grounds for the approach to the occupational hazard assessment. To complete the purpose, it is proposed to analyze the existing methods and approaches to the occupational hazard assessment and an approach to the occupational hazard assessment is proposed, which is based on the use of statistics on occupational injuries rates. The necessity of application of information systems for occupational hazard assessment is emphasized.
Keywords: hygiene and labor safety; occupational hazard; operative management; planning; information system